Interactive effects of advertising platform credibility and partisanship on advertising evaluation and recall. Issue 2 (4th May 2019) - Park, Chang Sup
ABSTRACT: This research examined how partisan media as a campaign ad platform affect voters, focusing on partisanship, ad platforms, and ad platform credibility. In a 3 (conservative party supporters, liberal party supporters, nonpartisans) × 2 (conservative and liberal ad platforms) × 2 (a high level and a low level of ad platform credibility) factorial design, participants saw a campaign ad surrounded by either a conservative medium or a liberal medium. The results reveal that nonpartisans' perception of platform credibility makes a significant difference in the recall of the ad, while partisans' perception of platform credibility did not, which suggests that nonpartisans' heuristic information processing can translate into systematic information processing in political advertising.